Classification of healthcare-associated infection: a systematic review 10 years after the first proposal - Cardoso, T. (2014)
BACKGROUND: Ten years after the first proposal, a consensus definition of healthcare-associated infection (HCAI) has not been reached, preventing the development of specific treatment recommendations. A systematic review of all definitions of HCAI used in clinical studies is made. METHODS: The search strategy focused on an HCAI definition. MEDLINE, SCOPUS and ISI Web of Knowledge were searched for articles published from earliest achievable data until November 2012. Abstracts from scientific meetings were searched for relevant abstracts along with a manual search of references from reports, earlier reviews and retrieved studies. RESULTS: The search retrieved 49,405 references: 15,311 were duplicates and 33,828 were excluded based on title and abstract. Of the remaining 266, 43 met the inclusion criteria. The definition more frequently used was the initial proposed in 2002--in infection present at hospital admission or within 48 hours of admission in patients that fulfilled any of the following criteria: received intravenous therapy at home, wound care or specialized nursing care in the previous 30 days; attended a hospital or hemodialysis clinic or received intravenous chemotherapy in the previous 30 days; were hospitalized in an acute care hospital for ≥2 days in the previous 90 days, resided in a nursing home or long-term care facility. Additional criteria founded in other studies were: immunosuppression, active or metastatic cancer, previous radiation therapy, transfer from another care facility, elderly or physically disabled persons who need healthcare, previous submission to invasive procedures, surgery performed in the last 180 days, family member with a multi-drug resistant microorganism and recent treatment with antibiotics. CONCLUSIONS: Based on the evidence gathered we conclude that the definition initially proposed is widely accepted. In a future revision, recent invasive procedures, hospitalization in the last year or previous antibiotic treatment should be considered for inclusion in the definition. The role of immunosuppression in the definition of HCAI still requires ongoing discussion.